1987
DOI: 10.1161/01.hyp.9.4.398
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic characteristics of sodium-sensitive human subjects.

Abstract: SUMMARY Fifty-eight normal subjects and 51 subjects with borderline hypertension underwent microvascular and hemodynamic studies while on an ad libitum diet and during periods of sodium depletion (10 mEq/day) and repletion (200 mEq/day). Hemodynamic measurements included arterial blood pressure, cardiac index, total peripheral resistance, forearm blood flow, vascular resistance, venous compliance, and capillary filtration fraction. Studies of the mlcrocirculation consisted of macrophotography of the buibar con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
73
2

Year Published

1988
1988
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 28 publications
8
73
2
Order By: Relevance
“…Using the criteria reported by Sullivan et al, 25 subjects with a 5% increase in MAP from levels before sodium loading were considered sodium sensitive. Subjects with less than 5% increase in MAP were classified as sodium insensitive.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the criteria reported by Sullivan et al, 25 subjects with a 5% increase in MAP from levels before sodium loading were considered sodium sensitive. Subjects with less than 5% increase in MAP were classified as sodium insensitive.…”
Section: Resultsmentioning
confidence: 99%
“…In a young adult population, Sullivan et al 25 reported an association of sodium sensitivity with elevation of forearm vascular resistance in both normotensive and borderline hypertensive individuals.…”
Section: -29mentioning
confidence: 99%
See 1 more Smart Citation
“…Medical personnel performed a physical examination, a comprehensive medical history, electrocardiogram (EKG) and obtained blood and urine samples to ensure that the participants met the study entry criteria. Each qualifying subject participated in a 12-day experiment consisting of six days on a low sodium diet followed immediately by six days on a high sodium diet, similar to those in previous studies laboratories (Sullivan, Prewitt, Ratts, Josephs, & Connor 1988;Anderson et al, 1998;Coruzzi, et al, 2005). Participants were given low sodium-low potassium meals in insulated containers, and provided with dietary logs to record food intake to augment adherence to the diet.…”
Section: Methodsmentioning
confidence: 99%
“…The number of subjects included in the present study was based on data indicating that the critical detectable differences in total peripheral resistance (TPR) measured at rest for differentiating between groups of normotensive versus hypertensive subjects was 23%, 19 of normotensive versus borderline hypertensive subjects was 32%, 20 and of normal and borderline hypertensive salt-sensitive versus salt-insensitive subjects was 44%. 21 The parents of the participants were identified as normotensive (systolic pressure <140 mm Hg and diastolic pressure <90 mm Hg) or hypertensive (systolic pressure >140 mm Hg or diastolic pressure >90 mm Hg) by personal telephone calls, or on the basis of replies to a questionnaire given to participants to assess their parents' medical blood pressure histories. Most of the parents with hypertension had stage II (moderate) hypertension and all were receiving pharmacological treatments, with some parents receiving pharmacological and nonpharmacological treatments for the condition.…”
Section: Methods Subjectsmentioning
confidence: 99%